Factors affecting total loan financing Agrocash-i effect with inflation rate, consumer price index and base lending rate / Elly Syahira Ramli - Ramli, Elly Syahira (Faculty of Business and Management, 2010)
Many people have financial problems at some point or another. Usually, financial difficulties start when a person expenses become greater than their income. Demand for personal loans increasing day by days. Personal loans are loans that are raised for personal use of an individual and money’s borrow to meet personal needs. Most nationalized, foreign and co-operative banks offer personal loans. Besides banks, other financial companies and institutions also offer the same loans. Most people begin with comparing the interest rate and term of loan amongst this financial institution as an initial screening before applying for personal loan.